Space : A Journey of Discovery - Kratzenberg-Annies, Volker (New York Harry N. Abrams, 2005)
Featuring images of Space taken by the European Space Agency, this title also includes images taken by astronauts, satellites, automatic probes, and the Hubble Space Telescope. These sources give an insight into our home planet, the other planets in our solar system and their moons, as well as asteroids, comets, stars and far away galaxies.
Include Color Illustrations.
A Journey of Discovery.
Keywords: Outer space -- Solar system